Benzo[a]pyrene diol epoxide-DNA cis adduct formation through a trans chlorohydrin intermediate - Meehan, Thomas (The National Academy of Sciences of the USA, 1997)
Alkylation of DNA by 7r,8t-dihydroxy,9t,10t-epoxy-7,8,9,10-tetrahydrobenzo[a]pyrene (anti-BPDE) forms mainly trans adducts (with respect to the C-9/10 positions). We recently described a halide-catalyzed pathway that preferentially generates cis adducts and now report that the trans chlorohydrin of anti-BPDE (trans-BPDCH) is an intermediate in the chloride-catalyzed reaction. trans-BPDCH was synthesized, and both it and anti-BPDE were reacted with deoxyadenosine as a model DNA nucleophile. The stereochemistry and yields of deoxyadenosine adducts were determined as a function of chloride concentration. In the absence of salt, the fraction of cis adducts obtained from anti-BPDE and trans-BPDCH are 0.33 and 0.67, respectively. Adding sodium chloride increases the fraction of cis adducts (and consequently decreases the fraction of trans adducts), with the midpoint of the increase for both substrates at approximately 35–40 mM chloride. The chloride-dependent curves for BPDE and BPDCH converge at 1 M chloride, where the fraction of cis adducts is 0.88. Chloride also increases the total yield of cis adducts with either substrate, whereas the yield of trans adducts from the chlorohydrin is not significantly changed. These results support a mechanism by which chloride ion undergoes nucleophilic addition to the benzylic C-10 position of anti-BPDE. This generates a trans halohydrin that alkylates DNA with inversion of configuration to form a cis adduct. This pathway may have biological significance because chlorohydrins could form in serum or in cells with relatively high intracellular concentrations of chloride.